Process development of inhalation powders containing simvastatin loaded liposomes using spray drying technology - Barbălată Cristina-Ioana; Porfire Alina Silvia; Ambrus Rita; Mukhtar Mahwash; Farkas Árpád; Tomuţa Ioan (2024)
The development of an inhalation powder (IP) for cancer therapy is desired to improve the therapeutic response and patient compliance. The latest studies highlighted that statins, a class of drugs used in hypercholesterolemia, can have anticancer and antiinflammatory properties. Therefore, the aim of the study was to develop an IP containing liposomes loaded with simvastatin using spray drying technology, as well as to investigate the influence of formulation factors on the quality attributes of the IP by means of experimental design. Results highlighted that the composition of liposomes, namely type of phospholipid and cholesterol concentration, highly influences the quality attributes of IP, and the use of optimal concentrations of excipients, i.e. D-mannitol and L-leucine, is essential to preserve the characteristics of liposomes throughout the spray drying process. The in vitro characterization of the optimal IP formulation revealed that the total percentage of released drug is higher from the IP formulation compared to the powder of active substance (53.38 vs. 42.76%) over a period of six hours, and 39.67% of dry particles have a size less than 5 µm, making them suitable for inhalation. As a conclusion, spray drying technology can be effectively used in the development and preparation of IP containing liposomes. © 2023 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Farmakológia és gyógyszerészet